Multimodal coordination enhances the responses to an avian duet. (18th December 2017) - Ręk, Paweł
Abstract : In many group-living animals, pairs sing together to cooperatively defend resources but such signals can be more complex than the acoustic component alone. In addition to songs, cooperating individuals may produce movements that can be precisely combined in many configurations, creating well organized audio-visual dances. Experiments with robot birds revealed that coordination of vocal and visual components of the Australian magpie-lark audio-visual display enhances the receiver's responses to this complex signal. Abstract: Animals communicate with their whole bodies, so their signals can be complex and multimodal. The joint intelligibility of multimodal signal components depends on their temporal coordination, which, when only one signaler is involved, depends on the synchronization between the different modalities of signals involved. Coordination is a challenge, however, in cooperatively signaling species because it requires continuous monitoring of the partner's behavior. Previous research showed that vocal coordination between cooperating individuals increases the perceived threat of the display; little is known, however, about the influence of multimodal coordination on the communication behavior of receivers to cooperative displays. I tested the function of multimodal coordination in the duets of the Australian magpie-lark Grallina cyanoleuca . I used a male–female pair of robot models to manipulate the temporal coordination between individuals and between sensory modalities. Precise coordination of the vocal and visual components of duets increased the perceived territorial threat of these joint displays. However, displays coordinated between individuals but not between modalities, and displays coordinated between modalities but not between individuals, were less effective, suggesting that the lack of coordination in one channel cancels benefits of coordination in the other. This study shows that multimodal coordination within individuals, in addition to coordination within modalities between individuals, enhances the perceptual integration and efficiency of avian duets.